HOLISTIC CHARACTER EDUCATION AT KHALAFIYAH ISLAMIC BOARDING SCHOOL: AN INTEGRATIVE APPROACH IN MATHLAUL HUDA CIPARAY ISLAMIC BOARDING SCHOOL - Asnawi, Asnawi; Sukandar, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyse the implementation of character education at Pondok Pesantren Mathlaul Huda Ciparay, which combines formal and non-formal curriculum in shaping the character of students. This research uses a qualitative approach with observation methods and in-depth interviews with pesantren administrators and teachers. The results showed that character education at Pondok Pesantren Mathlaul Huda was carried out through the exemplary approach, strengthening moral values, and disciplinary training. The ustadz acts as a model of behaviour that shows discipline and responsibility, which is then imitated by the santri in their daily lives. In addition, special programmes such as Ta'lim wa Tarbiyah and mutual cooperation activities strengthen moral and social values in santri. The influence of this character education can be seen in the social attitudes of santri who are more tolerant, empathetic, and have high social responsibility. In conclusion, an integrated approach that includes moral knowledge, feelings, and actions at Mathlaul Huda Islamic Boarding School has succeeded in shaping the character of students holistically. This research suggests that the character education model in this pesantren can be applied in other educational institutions as an effort to build the character of the younger generation with integrity.